Olive Stone Delignification Toward Efficient Adsorption of Metal Ions - Gao, Ying; Aliques Tomas, Maria del Carmen; Garemark, Jonas; Sheng, Xia; Berglund, Lars; Li, Yuanyuan (Frontiers in Materials, 2021)
Olive stone is an important biomaterial waste product generated in large amount. As a lignocellulose material, olive stone could be a sustainable resource for biosorbents. In this work, olive stone powder delignification using sodium chlorite (NaClO2) was performed to enhance metal ion adsorption capacity. The influence of the treatment on olive stone powder physical-chemical properties was studied, including specific surface area, surface chemistry, morphology, etc. The white, delignified olive stone powder was applied for metal ions (Fe3+, Cu2+, and Zn2+) adsorption. Olive stone delignification not only increases the accessibility of the olive stone powder but also broadens the applications to materials design with optical functions by the generation of a white powder.